Correlation Between Drug-Related Problems and the Treatment Cost for Geriatric Ischemic Stroke Patients in Tulungagung - nugraha, dhanang prawira; aditya, martanty (UI Scholars Hub, 2025)
Ischemic stroke was one of the diseases that frequently occurred in geriatric patients, while hemorrhagic stroke had a higher prevalence. Geriatric patients who experienced a stroke were not exempt from drug-related problems (DRP) due to the complexity of treatment and comorbid factors they encountered. This study aimed to determine the correlation between DRP and the cost of care for ischemic stroke patients, particularly in the geriatric population. The study design was cross-sectional, with data collected retrospectively, and the sample comprised 53 geriatric stroke patients who met the inclusion and exclusion criteria. DRP was assessed using the PCNE 6.2 criteria, and the cost data included expenses for medications, medical devices, laboratory tests, visit fees, accommodation, diagnostic electromedical procedures, radiology, nutrition, and insurance. The independent variable in this study was DRP, while the dependent variable was the cost of care. The analysis used in this study was Spearman's correlation and was presented with a correlation coefficient (R). The results showed a significant correlation between DRP and care costs (p-value < 0.05), with a correlation coefficient 0.501. The study concluded with the assertion that an increase in DRP is associated with elevated costs of care for geriatric ischemic stroke patients.